What the European and American welfare states have in common and where they differ: Facts and fiction in comparisons of the European social model and the United States - Jens Alber (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2009)
This paper examines to what extent the classification of the American welfare state as "residual" squares with the empirical facts. Section I describes key features of American social policy developments. The U.S. system is clearly dominated by public provisions for welfare among which social insurance programs, especially Social Security and Medicare, represent the lion's share, and public pensions are more universal, redistributive, and generous than in some European countries. Noteworthy differences remain with respect to the stronger reliance on private provisions in pensions and health, the emphasis on work-conditioned benefits and a greater importance of selective schemes. The terms "work-conditioned welfare" or "corporate citizenship" adequately capture these key features by highlighting that employers are gatekeepers of social entitlements. Section II examines if key features of the American welfare state have recently become more prominent in Europe. A slight approximation to the American model is found with respect to a growing importance of private expenditure for pensions and health, but not with respect to a greater selectivity of benefits. On the level of policy discourse, the idée directrice of European social policies is changing from social protection to activation, as three traditionally American elements have come to prominence: an emphasis on individual responsibility, on the private supply of services and more consumer choice, and on the activation of people at working age. Yet there is no general convergence towards the American model, because the United States is approximating Europe with respect to health insurance while public attitudes are shifting in favour of extended state responsibilities. Hence there is a complex pattern of specific policy learning rather than convergence towards one model of social policy. In sum, similarities between social policies in Europe and America are found to be more noteworthy than the term "residual welfare state" for the U.S. suggests.
Keywords: 300; Sozialstaat; Sozialpolitik; Öffentliche Sozialausgaben; Vergleich; USA; EU-Staaten